TRANSFORMING VOCATIONAL EDUCATION THROUGH ARTIFICIAL INTELLIGENCE: COMPETENCY DEVELOPMENT FOR THE DIGITAL ECONOMY (Ustozlar uchun, 2026)
Artificial Intelligence (AI) technologies play a crucial role in shaping student competencies in vocational education and preparing them for the digital economy. This article analyzes the advantages, pedagogical approaches, and practical outcomes of implementing AI-based adaptive learning systems in Uzbek technical schools and colleges. The results indicate that AI integration enables students to follow individualized learning paths, enhances their skills, and prepares them for labor market competencies required in the digital economy.